Promoting Local Geodiversity Through Experiential Outdoor Education: The Syros Island Initiative - Theodora Tsipra; Hara Drinia (Heritage, 2025)
This study reviewed the benefits of outdoor activities and educational programs that take place in nature in terms of the cognitive and mental development of children. Research has highlighted the benefits offered to children by their participation in experiential activities that take place outdoors and are related to natural phenomena. These activities help children realize how important it is to conserve nature and protect sites of world heritage, thus becoming active citizens in the future. In this study, the uniqueness of Syros Island is presented, emphasizing the need for the world-renowned geological heritage of Syros to be preserved and promoted, both for the scientific community and for the public, with the aim of establishing a geopark in Apano Meria, as proposed by local authorities, along with a local museum. In this context, a working methodology was developed involving the design and implementation of a pilot educational program combining field-based activities, guided interpretation, and interactive learning tools. An indicative educational program was piloted with primary and secondary school students, as well as postgraduate students from the University of Athens. Recognizing the important role of geoparks in school education, the program focused on the rare geological phenomena on the northern side of Syros and was adapted to the characteristics of each participant age group.